DIGITAL LITERASI: SEBAGAI UPAYA DALAM MEMENUHI KEBUTUHAN INFORMASI SIVITAS AKADEMIKA UNIVERSITAS BANGKA BELITUNG (STUDY KASUS DI PERPUSTAKAAN UNIVERSITAS BANGKA BELITUNG) - Arja Kusuma (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
Information is the core of all development processes, includingtheenvironment of Bangka Belitung University, where the learning process and the development of knowledge occur. The library of Bangka Belitung University as one of the technical implementing units, has a role in providing the information, especially the information that is credible, relevant, up to date and proportionate despite the funding, policy and management constraints faced by the library in carrying out the information. The presence of digital technology, internet and communication tools provides opportunities for the library of Bangka Belitung University in developing collections at the Bangka Belitung University Library. This study aimsto findout the efforts of the Bangka Belitung University library related to digital literacy as an effort to meet the information needs of the academic community of Bangka Belitung University? The method used was qualitative, and the datawere collected using the partisivan observation and documents. The study reveals three findings as follows: first, the Bangka Belitung University Library tried to build digital literacy competence for librarians through training activities, technical guidance and workshop, second, maximizing digital literacy competence in collecting, storing and disseminating information in the library of Bangka Belitung University and third, building digital literacy competence for users and / or students.